1995
DOI: 10.1128/aac.39.2.422
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance in Candida albicans: disruption of the BENr gene

Abstract: The BENr gene of Candida albicans, which confers resistance on susceptible strains of Saccharomyces cerevisiae to six structurally and functionally unrelated drugs, was described recently (R. Ben-Yaacov, S. Knoller, G. Caldwell, J. M. Becker, and Y. Koltin, Antimicrob. Agents Chemother. 38:648-652, 1994). This gene bears similarity to membrane proteins encoding antibiotic resistance in prokaryotes and eukaryotes. The effect of disruption of this gene on viability and drug susceptibility was determined. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 32 publications
3
55
0
Order By: Relevance
“…The lack of dominance of the wild-type allele to the null allele has also been reported for the Candida drug transporter CaMDR and the Candida MKC1 gene, a homolog of the Saccharomyces MAPK SLT2͞MPK1. The heterozygotes of null mutations of these genes are more sensitive to inhibitors than the wild type (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of dominance of the wild-type allele to the null allele has also been reported for the Candida drug transporter CaMDR and the Candida MKC1 gene, a homolog of the Saccharomyces MAPK SLT2͞MPK1. The heterozygotes of null mutations of these genes are more sensitive to inhibitors than the wild type (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans cells lacking the MDR1 gene are hypersensitive to most of the drugs listed above (20). In two FLC R clinical isolates, deletion of MDR1 abolished the drug resistance phenotype of these strains, demonstrating that in these strains, fluconazole resistance was dependent on the overexpression of MDR1 (55).…”
mentioning
confidence: 97%
“…Overexpression and gene inactivation studies have shown that MDR1 confers specific resistance to fluconazole, benomyl, cycloheximide, benzotriazole, methotrexate, 4-nitroquinoline-N-oxide (4-NQO) and sulfomethuron methyl (Ben-Yaacov et al, 1994;Fling et al, 1991;Goldway et al, 1995;Wirsching et al, 2000b). Disruption of MDR1 causes an increased susceptibility to methotrexate, cycloheximide and 4-NQO (Goldway et al, 1995;Sanglard et al, 1996).…”
Section: Introductionmentioning
confidence: 99%